Mechanical and Bond-Slip Properties of Steel-Fiber-Reinforced Geopolymer Recycled-Aggregate Concrete - Jianhua Ji; Zening Zhang; Yi Zhang; Xi Liu (Buildings)
Steel-fiber-reinforced geopolymer recycled-aggregate concrete (SFGRC) represents a promising low-carbon building material, yet data on its bond behavior remains scarce, limiting its structural application. To study the mechanical properties and bond strength of SFGRC, five groups of different mix proportions were designed. The main variation parameters were the content of recycled aggregate and the volume content of steel fiber. The cube compressive strength, splitting tensile strength, and flexural strength tests of SFGRC were completed. The influence law of different anchorage lengths on the bond strength between steel bars and SFGRC was studied through the central pull-out test. A multi-parameter probability prediction model of bond strength based on Bayesian method was established. The results show that with the increase of the content of recycled aggregate, the compressive strength of the specimen shows a downward trend, but the tension-compression ratio is increased by 18–22% compared to concrete with natural aggregates at equivalent strength grades. The content of steel fiber can significantly improve the mechanical properties of SFGRC. The bond strength between steel bars and SFGRC is 14.82–17.57 MPa, and the ultimate slip is 0.30–0.38 mm. A probability prediction model of ultimate bond strength is established based on 123 sets of bond test data. The mean and covariance of the ratio of the predicted value of the probability model to the test value are 1.14 and 2.61, respectively. The model has high prediction accuracy, and continuity and can reasonably calculate the bond strength between steel bars and SFGRC. The developed Bayesian model provides a highly accurate and reliable tool for predicting SFGRC bond strength, facilitating its safe and optimized design in sustainable construction projects.